1999
DOI: 10.1063/1.371698
|View full text |Cite
|
Sign up to set email alerts
|

Electrical and structural characteristics of lanthanum-doped barium titanate ceramics

Abstract: Single phase La-doped BaTiO 3 with the formula Ba 1Ϫx La x Ti 1Ϫx/4 O 3 : 0рxр0.20 was prepared by solid state reaction of oxide mixtures at 1350°C, 3 days, in O 2 . The tetragonal distortion in undoped BaTiO 3 decreased with x and samples were cubic for xу0.05. Both the tetragonal/cubic and orthorhombic/tetragonal transition temperatures decreased with x, but at different rates, and appeared to coalesce at xϳ0.08. The value of the permittivity maximum at the tetragonal/cubic phase transition in ceramic sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
239
1
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 345 publications
(262 citation statements)
references
References 21 publications
21
239
1
1
Order By: Relevance
“…[1][2][3] Its high permittivity, coupled with temperature stability through the use of suitable dopants, make BaTiO3 an excellent candidate for the fabrication of multilayer capacitors. [4][5][6][7] More recently it has received renewed interest as the basis for the fabrication of lead-free piezoelectric devices. 8 Traditionally, oxide-based electroceramics such as BaTiO3 have been made via solid-state synthesis, 9 which whilst reliable, suffers from several inherent drawbacks.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Its high permittivity, coupled with temperature stability through the use of suitable dopants, make BaTiO3 an excellent candidate for the fabrication of multilayer capacitors. [4][5][6][7] More recently it has received renewed interest as the basis for the fabrication of lead-free piezoelectric devices. 8 Traditionally, oxide-based electroceramics such as BaTiO3 have been made via solid-state synthesis, 9 which whilst reliable, suffers from several inherent drawbacks.…”
Section: Introductionmentioning
confidence: 99%
“…The literature data mainly reports the preparation of lanthanum doped BT by solid state reaction [3][4][5][6]. Among the several soft chemistry routes that can be used, the polymeric precursor method has the advantage of assuring chemical purity of the final product what is very important for final properties of obtained material.…”
Section: Introductionmentioning
confidence: 99%
“…The grain size also influences the dielectric response (Fang et al, 1993;Hoshina et al, 2008), but there are the intrinsic effects due to the introduction of cations in the A and B sites of the ABO 3 structure. More precisely, when donor-type doping of KNN with La +3 and Ta +5 is performed (Hao et al, 2009) and in BaTiO 3 (Morrison et al, 1999), the dielectric constant at the T C decreases and the transition became broad, this behavior it is not well understood but it is suggested that the many different transitions collapse at once resulting in the broad pick at T C . In the KNLNT it seems that the Ta +5 doping induces that the ε r was lower at the transition compared with pure KNN, the contribution of grain size was discarded.…”
Section: Piezoelectric Dielectric and Ferroelectric Properties Of Knlntmentioning
confidence: 99%